Montalbano's first case and other stories - Camilleri, Andrea (Camilleri, Andrea. Inspector Montalbano mystery., 2016)
"From the author of the New York Times-bestselling Inspector Montalbano mystery series, twenty-one short stories spanning the beloved detective's career. Inspector Montalbano has charmed readers in nineteen popular novels, and now in Montalbano's First Case and Other Stories, Andrea Camilleri has selected twenty-one short stories, written with his trademark wit and humor, that follow Italy's famous detective through highlight cases of his career. From the title story, featuring a young deputy Montalbano newly assigned to Vigata, "Montalbano Says No," in which the inspector makes a late-night call to Camilleri himself to refuse an outlandish case, this collection is an essential addition to any Inspector Montalbano fan's bookshelf and a wonderful way to introduce readers to the internationally bestselling series"--